Rad51 Paralog Complexes BCDX2 and CX3 Act at Different Stages in the BRCA1-BRCA2-Dependent Homologous Recombination Pathway - Chun, Jarin (American Society for Microbiology, 2013)
The Rad51 paralogs are required for homologous recombination (HR) and the maintenance of genomic stability. The molecular mechanisms by which the five vertebrate Rad51 paralogs regulate HR and genomic integrity remain unclear. The Rad51 paralogs associate with one another in two distinct complexes: Rad51B-Rad51C-Rad51D-XRCC2 (BCDX2) and Rad51C-XRCC3 (CX3). We find that the BCDX2 and CX3 complexes act at different stages of the HR pathway. In response to DNA damage, the BCDX2 complex acts downstream of BRCA2 recruitment but upstream of Rad51 recruitment. In contrast, the CX3 complex acts downstream of Rad51 recruitment but still has a marked impact on the measured frequency of homologous recombination. Both complexes are epistatic with BRCA2 and synthetically lethal with Rad52. We conclude that human Rad51 paralogs facilitate BRCA2-Rad51-dependent homologous recombination at different stages in the pathway and function independently of Rad52.